AQUEOUS HIGH-TEMPERATURE AND HIGH-PRESSURE ORGANIC GEOCHEMISTRY OF HYDROTHERMAL VENT SYSTEMS - Simoneit B.R.T. (My University, 1993)
Hydrothermal systems associated with oceanic spreading centers are now recognized as relatively common phenomena, and the organic chemical alterations occurring there are rapid and efficient. In the marine hydrothermal systems at water depths > 1.5 km, the conditions driving chemical reactions are high temperatures (up to >400 degrees C), confining pressures (>150 bar), and other parameters such as pH, Eh, and mineralogy in an aqueous open flow medium. Continental hydrothermal systems may also be of interest, as, for example, in failed or dormant rifts and regions around piercement volcanoes. Organic matter alteration by reductive reactions to petroleum hydrocarbons occurs in hydrothermal systems over a wide temperature window (approximately 60 to >400 degrees C), under elevated pressure, and in a brief geological time (years to hundreds of years). The products are rapidly moved as bulk phase or in fluids from the regions at higher temperatures to areas at lower temperatures, where the high molecular weight material separates from the bulk. These conditions are conducive to organic chemistry which yields concurrent products by primarily reduction (due to mineral buffering), oxidation (high thermal stress), and synthesis reactions. This chemistry is just beginning to be elucidated by the geochemical community, but there are various industrial applications which provide useful preliminary insight. Therefore, the behavior of organic matter (inclusive of methane to high molecular weight compounds > C40) in warm to supercritical water needs to be characterized to understand the implications of this novel phenomenon in geological and geochemical processes, and the chemistry occurring over the full temperature spectrum of hydrothermal systems is of relevance to origins of life research.